New diagnostic methods and some concepts hemo blood infection - Escomel, Edmundo (1920)
In order to better study blood leukocytes and some hematological parasite infections, we have used the procedure heritrolísis that dissolving all RBCs, leaving visible only to leukocytes and blood parasites. As these are in a state of high dilution in the blood, it has been necessary to find, by centrifuging, which uniquely enhances their study, and therefore the diagnosis in many parasitemias.